Formulasi Baru K-Means dalam Pengelompokkan Desa Berdasarkan Ketersediaan Fasilitas Kesehatan - Lestari, Indah; Suliadi (Jurnal Riset Statistika, 2025)
Abstract. K-Means is a popular data clustering method but has limitations in optimizing its objective function. The Lloyd algorithm, as the standard approach to K-Means, also has several weaknesses: 1) It is heuristic and does not guarantee a globally optimal solution; 2) It is highly sensitive to the initialization of cluster centers; 3) It often converges to suboptimal solutions; and 4) It requires distance calculations between samples and centers at each iteration, increasing computational load and storage cost. To address these shortcomings, Nie et al. (2023) proposed a new formulation of K-Means Clustering with the following advantages: 1) It does not require updating cluster centers in every iteration; 2) It needs fewer auxiliary variables; 3) It yields effective and stable results; and 4) It has a faster convergence rate. In this study, the new formulation of K-Means is implemented to cluster villages/sub-districts in West Java Province based on the availability of healthcare facilities. The data used are derived from the Health Sector of the Social Resilience Index in the Village Development Index, consisting of 14 variables and 5,312 village units. Based on the analysis, villages/sub-districts can be grouped into three clusters: Cluster 1 contains 34 villages, Cluster 2 has 21 villages, and Cluster 3 includes 5,257 villages, that gives silhouette score of 0.9160, indicating a strong cluster structure. Abstrak. K-Means merupakan metode pengelompokan data yang populer, namun memiliki keterbatasan dalam optimasi fungsi tujuannya. Algoritma Lloyd sebagai pendekatan umum K-Means juga memiliki kelemahan sebagai berikut: 1) Bersifat heuristik sehingga tidak menjamin solusi optimal; 2) Sensitif terhadap inisialisasi k pusat; 3) Sering berhenti pada solusi kurang optimal; dan 4) Memerlukan perhitungan jarak antar sampel dan pusat pada setiap iterasi, yang meningkatkan beban komputasi serta storage cost. Untuk mengatasi kekurangan tersebut, Nie et al. (2023) mengusulkan formulasi baru K-Means Clustering dengan keunggulan: 1) Tidak perlu menghitung pusat cluster di setiap iterasi; 2) Memerlukan lebih sedikit variabel tambahan; 3) Memberikan hasil yang efektif dan stabil; serta 4) Memiliki tingkat konvergensi lebih cepat. Penelitian ini menerapkan formulasi baru K-Means untuk mengelompokkan 5.312 Desa/Kelurahan di Jawa Barat berdasarkan 14 indikator kesehatan pada Indeks Ketahanan Sosial (IKS). Hasil analisis menunjukkan bahwa desa-desa tersebut terbagi ke dalam tiga cluster. Cluster 1 terdiri atas 34 desa/Kelurahan, cluster 2 terdiri dari 21 desa/Kelurahan, dan cluster 3 terdiri dari 5.257 desa/Kelurahan, yang memberikan nilai silhouette sebesar 0,9160 yang menunjukkan struktur cluster yang kuat.